Pharmaceutical Drug Pricing In Malaysia: An Assessment Of Perception, Mechanisms, And International Comparisons - Shukeri, Mohammad Amirul Ashraf Mohammad (2023)
High drug price is a hot topic in Malaysia. This thesis attempts to analyze the nature of pharmaceutical pricing in Malaysia using qualitative and quantitative studies. The study was structured into seven workstreams, ranging from current policies and strategies, comparison with other countries, perception of the public on the drug price, policy analysis and pharmacoeconomic analysis. Workstream One, Two, Three, Five and Six are qualitative studies and Workstream Five and Seven are quantitative studies. Workstream One, Two, and Three are systematic reviews, conducted by searching for peer-reviewed articles in major electronic databases such as PubMed, Scopus, and ScienceDirect. Workstream One gathers information on the current medicine price in Malaysia. Workstream Two analyzed the difference between Malaysia's pharmaceutical policies and Western countries. Workstream Three compared Malaysia and Italy's financial agreements with pharmaceutical manufacturers. Workstream Four is a cross-sectional study, analyzing the perception of the public towards the drug price in Malaysia. Workstream Five compared the drug price in the Malaysian government sector with Australia by matching the drug database. Workstream Six is a policy analysis involving external reference pricing (ERP), performed using Reich's PolicyMaker tool and Kingdon's multiple stream framework to elucidate the stakeholders' interest and power, as well as potential challenges to the policy implementation.